Razumevanje logistične platforme v teoriji in praksi - Gajšek, Brigita (visokošolska dela, 2014)
In the scientific literature, the term logistics platform is increasingly used in recent years. But it happens that authors use the term logistics platform in contextually diverse ways. In parallel, they do not present a comprehensive theoretical model that would facilitate its practical implementation in accordance to the knowledge of its likely benefits and in compliance with current strategies. Consequently we have approached to study logistics platforms in a balanced way, with qualitative and quantitative approach. We want to help clarify understanding of the logistic platform concept so as to release its potential for the benefit of the logistics sector. Cross-sectional research was conducted in Slovenia, Poland and Singapore. Web-based survey responses were obtained from four organization types: logistics companies; production or service non-logistics companies; branch associations / state agencies / chambers of commerce; and educational institutions. Logistics platforms are a very much a multi-level phenomenon which, through macro-level organization, may multiply the micro- and meso-level effects obtained. The joint development of promising inter-organizational concepts which involves different stakeholder groups can be inefficient owing to differences in concept content understanding. Our survey has confirmed the proposed general logistics platform theoretical model regarding constituents and geographical/business areas. Moreover, our international comparison reveals some statistically significant differences in perceptions. Although all the respondents have access to a single global database, it is clear that an understanding of the concept could be additionally influenced by local factors which, as such, may promote or inhibit international integration and should be further investigated. We propose a general logistics platform model and seek to raise awareness of the complexity surrounding the implementation of this particular inter-organizational concept. From the viewpoint of practitioners, the knowledge that different stakeholder groups may have divergent perceptions of the concept's content is important and will help strengthen inter-organizational projects by devoting attention to basic fact unification. Through this study we offer to the academics wide possibilities for further research.
Keywords: disertacije; external integration; logistics; logistics platform; logistična platforma; logistika; model; razumevanje koncepta; understanding of the concept; zunanja integracija